Effectiveness of lifestyle and psychosocial interventions in reducing cognitive decline in older people: Systematic review: Dementia care research: Behavioral interventions. (7th December 2020) - Mansour, Hassan; Whitty, Emma; Aguirre, Elisa; Palomo, Marina; Charlesworth, Georgina; Ramjee, Serena; Poppe, Michaela; Brodaty, Henry; Kales, Helen C; Morgan‐Trimmer, Sarah; Nyman, Samuel; Lang, Iain A; et al.
Abstract: Background: Observational findings suggest that a third of dementia cases are attributable to modifiable risk factors (Livingston et al, 2017). However, we are still unclear on what non‐pharmacological interventions should look like or what a manualised dementia prevention programme might include. Method: PubMed, EMBASE (Ovid), PsycINFO, CINAHL, Web of Science, and reference lists of included studies were systematically searched and screened by two independent reviewers. We included lifestyle and psychosocial interventions that aimed to reduce cognitive decline in healthy people aged 50+, and people of any age with Subjective Cognitive Decline or Mild Cognitive Impairment. We narratively synthesised evidence, prioritising results from studies rated at lower Risk of Bias (ROB) and used Centre for Evidence Based Medicine guidelines to grade levels of evidence. These findings were used to inform co‐production of an internationally collaborated APPLE‐Tree (Active Prevention in People at risk of dementia: Lifestyle, bEhaviour change and Technology to REducE cognitive and functional decline) programme. Result: A total of 64 studies were included describing psychosocial (n=12), multi‐domain (n=10), exercise (n=36) and dietary (n=6) interventions. We found Grade A evidence that 4+ months of aerobic exercise twice weekly had a moderate effect on global cognition. With interventions that integrate, cognitive and motor challenges (e.ge. dance or dumb bell training) had small to moderate effects on memory or global cognition. We also found Grade B evidence that 4+ months of creative art or storytelling groups; 6 months of resistance training and a two‐year, dietary, exercise, cognitive training and social intervention had small but positive effect on global cognition. Conflicting evidence was observed for interventions solely focusing on increasing Mediterranean diet adherence. With effects for some interventions remaining up to a year beyond facilitated sessions. Only two lower ROB studies measured impact of non‐pharmacological interventions onto dementia incidence with neither finding significant effects. Conclusion: Based on current published findings an evidence‐based intervention strategy to improve global cognition, memory and executive functioning should include group therapy carried out for 4+ months, promoting engagement in regular (at least weekly) activity, involving aerobic or resistance exercise, and cognitively demanding (visuospatial/memory) or creative tasks.